2022
DOI: 10.1186/s12864-022-08468-x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographic relationships and the evolutionary history of the Carassius auratus complex with a newly born homodiploid raw fish (2nNCRC)

Abstract: Background An important aspect of studying evolution is to understand how new species are formed and their uniqueness is maintained. Hybridization can lead to the formation of new species through reorganization of the adaptive system and significant changes in phenotype. Interestingly, eight stable strains of 2nNCRC derived from interspecies hybridization have been established in our laboratory. To examine the phylogeographical pattern of the widely distributed genus Carassius across Eurasia an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 104 publications
0
6
0
Order By: Relevance
“…This scenario of historical gene flow from east to west supported the existence of historical corridors for the dispersion of high-elevation species during periods of climate cooling (Antonelli et al, 2010; de Oliveira et al, 2021 ). However, we found a low level of migration rate in the opposite direction (a West-East pattern), which was uncommon in freshwater species found in China during the same or much older period, such as the frogs, snails, and fish (Yan et al, 2013; Gu et al, 2019 ; Gu et al, 2022 ). The authors suggested the role of Pleistocene interglacials dispersal in influencing the species diversification.…”
Section: Discussionmentioning
confidence: 56%
“…This scenario of historical gene flow from east to west supported the existence of historical corridors for the dispersion of high-elevation species during periods of climate cooling (Antonelli et al, 2010; de Oliveira et al, 2021 ). However, we found a low level of migration rate in the opposite direction (a West-East pattern), which was uncommon in freshwater species found in China during the same or much older period, such as the frogs, snails, and fish (Yan et al, 2013; Gu et al, 2019 ; Gu et al, 2022 ). The authors suggested the role of Pleistocene interglacials dispersal in influencing the species diversification.…”
Section: Discussionmentioning
confidence: 56%
“…In gynogenetic organisms, sperm is required to activate the egg but not incorporate its genetic material into the egg (Beukeboom and Vrijenhoek, 1998;Zhang et al, 2015). To maintain clonal lineages in natural populations, gynogens thus have to exploit males of sexual species, whose sperm is "wasted", acting as so-called "sexual parasites" (Alves et al, 2001;Bi and Bogart, 2010;Gu et al, 2022;Majtánová et al, 2016;Morishima et al, 2008a). Nevertheless, occasional failure to eliminate sperm pronucleus from the zygote leads to the emergence of triploid offspring (Alves et al, 1998;Lamatsch and Stöck, 2009;Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…However, the diploid form of C. gibelio was not included in that study. Other studies using mtDNA and hoxa2b gene sequences even suggested a more complex relationship between C. gibelio and C. auratus, where the monophyly of C. gibelio was not supported (115,116). In addition, gene ow was highlighted between the two species (88, 115), suggesting that C. gibelio and C. auratus were conspeci c and interfertile.…”
Section: Discussionmentioning
confidence: 98%